1991
DOI: 10.1111/j.1439-037x.1991.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Requirements of Safflower Entries in Middle Egypt

Abstract: Two promising selected land races of safflower (Carthamns tinctorious L.) designated as line 11 and line 13, together with the local variety Giza 1, were examined under three levels of moisture depletions, i.e. 40, 60 and 80 % ASMD at Fayoum, Middle Egypt during 1986/87 and 1987/88 seasons. In both growing seasons, the second irrigation treatment i.e. 60 % ASMD gave the highest means for growth characters as well as seed yield and most of its components. Seed oil content per cent exhibited an increased as soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
3
3
1
Order By: Relevance
“…Indeed, it was unexpected and the most striking result of this study. In safflower there is a general agreement that seed yield is increased by irrigation (Ibrahim et al 1991). However, the results of some research seem to support our finding that there has been no marked response to irrigation in safflower.…”
Section: Oil Contentcontrasting
confidence: 52%
See 1 more Smart Citation
“…Indeed, it was unexpected and the most striking result of this study. In safflower there is a general agreement that seed yield is increased by irrigation (Ibrahim et al 1991). However, the results of some research seem to support our finding that there has been no marked response to irrigation in safflower.…”
Section: Oil Contentcontrasting
confidence: 52%
“…Several studies have examined the effects of irrigation in safflower. The results indicated that under irrigated conditions it could be very productive (Ibrahim et al 1991).…”
mentioning
confidence: 66%
“…These findings could be attributed to the highly significant differences among seed yield due to irrigation treatments, as well as differences between water consumptive uses. These results are in line with those reported by Ibrahim et al (2008) who showed that the best water use efficiency (WUE) for seed production was obtained from irrigated safflower plants at 60 % of ASMD.…”
Section: Water Use Efficiency (Wue)supporting
confidence: 92%
“…This increase for seasonal water consumptive use at 45% of ASMD may be to higher water around root zone provides chance for more consumption of water that ultimately resulted in increasing transpiration by plants and evaporation from the soil surface. These results were in harmony with Katara and Bansal (1995) and Ibrahim et al (2008) who mentioned that water consumptive use by safflower plants increased as the available soil moisture around the root zone increased.…”
Section: Soil-water Relations: 21 Water Consumptive Use (Cu)supporting
confidence: 87%
See 1 more Smart Citation